THE EFFECT OF POLITICAL CONNECTIONS ON FINANCIAL PERFORMANCE: AN EMPIRICAL STUDY OF STATE-OWNED ENTERPRISES LISTED ON THE INDONESIAN STOCK EXCHANGE - Anggi Putri Kusuma Wardini; Alia Wulan Febrianti; Erik Nugraha; R. Rita Avianty (PT. Altin Riset Publishing, 2026)
This study examines the influence of political connections on the financial performance of state-owned enterprises (SOEs) listed on the Indonesia Stock Exchange. Political connections are considered an external factor that may provide firms with strategic advantages, such as access to government projects, regulations, and financial support, but may also create governance risks. The research employed a quantitative method with a descriptive-associative approach, using panel data from 15 SOEs over the 2020–2023 period. Data were collected from annual reports and financial statements, while financial performance was measured by Return on Assets (ROA). The results of regression analysis indicate that political connections have a positive and significant effect on financial performance, implying that the presence of politically connected individuals within the board of directors or commissioners enhances efficiency and profitability. These findings confirm the hypothesis that political connections play a strategic role in shaping SOEs’ financial outcomes. The study concludes that while political connections can be an intangible asset, their benefits should be balanced with strong corporate governance to minimize risks of political dependency and conflicts of interest.